2023
DOI: 10.1177/23259671231166012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age and Sex on Psychological Readiness and Patient-Reported Outcomes 6 Months After Primary ACL Reconstruction

Abstract: Background: Successful return to sport after anterior cruciate ligament (ACL) reconstruction (ACLR) can be affected by a patient’s physical and psychological state throughout the rehabilitation process. Purpose: To prospectively compare differences in patients at 6 months after primary ACLR with the ACL–Return to Sport after Injury (ACL-RSI), International Knee Documentation Committee (IKDC) or pediatric (Pedi)-IKDC, Hospital for Special Surgery Pediatric Functional Activity Brief Scale (Pedi-FABS), and Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…In terms of DIF, younger patients exhibited lower confidence and greater fear of reinjury, impacting their scores on the ACL‐RSI compared to older patients. This aligns with studies showing that emotional responses significantly affect younger athletes' psychological state towards RTS after ACL reconstruction [ 18 , 23 , 26 ].…”
Section: Discussionsupporting
confidence: 90%
“…In terms of DIF, younger patients exhibited lower confidence and greater fear of reinjury, impacting their scores on the ACL‐RSI compared to older patients. This aligns with studies showing that emotional responses significantly affect younger athletes' psychological state towards RTS after ACL reconstruction [ 18 , 23 , 26 ].…”
Section: Discussionsupporting
confidence: 90%
“… 91 , 92 Also, while both males and females are motivated to be physically active, male athletes may be more likely to endorse competition and winning as motivators for sports participation and, therefore, exhibit more risk-taking behaviours. 93 Milewski et al 94 reviewed 176 patients with a mean age of 17 years undergoing ACLR and found that female athletes had significantly higher levels of injury-related stress and lower levels of perceived psychological readiness to return to sport compared with at six months after surgery.…”
Section: Introductionmentioning
confidence: 99%